Evidence that spo0A mutations are recessive in spo0A-/spo0A+ merodiploid strains of Bacillus subtilis. - Trowsdale, J (1978)
The spo0A locus contains two types of closely linked mutations that block sporulation at stage 0: spo0A mutations (the most pleiotropic of the stage 0 markers) and spo0C mutations. It was previously thought that spo0A mutations were dominant in merodiploids of Bacillus subtilis, whereas spo0C mutations were recessive. We have shown that spo0A mutations were recessive when spo0A-/spo0A+ merodiploids were made in the genetic backgrounds of strains that were resistant to antibiotic produced by the wild-type strain. Reinvestigation of cultures of spo0A-/spo0A+ merodiploids constructed in the antibiotic-sensitive spo0A strain showed that they contained the spo0A allele at a low frequency, and they produced very few haploid Spo- segregants. These facts indicated that the cultures contained mostly homogenotic (spo0A+/spo0A+) cells. The reason for the poor survival of the spo0A-/spo0A+ merodiploids in the genetic background of the antibiotic-sensitive strain was not clear, but several possible explanations were given. It may have been related to the diploid state of other genes in the same merodiploid cells. The previous indication that spo0A mutations were dominant seems to have been based on the properties of a rare class of Spo- segregants that were probably selected in the presence of antibiotic.